A perspective on the potential health risks from PCBs and heavy metals contamination of M. merluccius from Mediterranean Sea. (17th February 2021) - Spognardi, Sara; Bravo, Ilenia; Rea, Riccardo; Cappelli, Lucio; Papetti, Patrizia
In this study, we determined the concentration of six marker PCBS congeners and four trace elements, all having a maximum tolerable level of intake set by EU regulation, in samples of European hake taken from the Mediterranean Sea. The results showed that the contaminant levels were below the recommended international limits in all samples, although with higher PCBs concentrations in samples from Ligurian and Adriatic Sea. The relationships between the contaminants and the sampling sites were investigated using analysis of variance (ANOVA) and Tukey's HSD post-hoc tests. Statistical analysis revealed significant interactions especially between the PCBs, the sum of PCBs and the sites. To evaluate the potential health risk from consumption, we calculated the estimated daily intake (EDI) for adults, finding that total health risk index (HRI) value was low (< 1) in the case of chronic consumptions, despite the non-negligible mercury concentration.